Kajian Konseptual dan Aplikasi Moderasi Beragama dalam Al-Qur’an - Rizal, Syamsul; Yasin, Arbi (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2024)
Abstract This study aims to understand the concept of moderation in the perspective of the Qur'an. In this study focuses on analyzing certain verses in the Qur'an that lead to the concept of moderation (wasathiyah) and understand its implications in various aspects of life. This research method involves the approach of analyzing the text of the Qur'an by using the approach of tafsir, taking the opinions of scholars and in-depth study of literature. The results show that the concept of moderation in the Qur'an is not only limited to aspects of ritual worship, but also extends into the moral, social, and political spheres. The Qur'an emphasizes the importance of being in the middle, avoiding extremism, and developing justice and wisdom in various aspects of human life. This research contributes to a broader understanding of the values and principles of moderation in Islam, in line with the perspective of the Qur'an. The implications of the findings of this study are expected to be the basis for the development of thinking and the implementation of moderation in the context of everyday life, which is in line with the teachings of the Qur'an. Keywords: Al-Qur'an, Tafsir, religious moderation Abstrak Penelitian ini bertujuan untuk memahami konsep moderasi dalam perspektif Al-Qur'an. Dalam penelitian ini memfokuskan dalam menganalisis ayat-ayat tertentu dalam al-Qur'an yang mengarahkan pada konsep moderasi (wasathiyah) serta memahami implikasinya dalam berbagai aspek kehidupan. Metode penelitian ini melibatkan pendekatan analisis teks Al-Qur'an dengan menggunakan pendekatan tafsir, mengambil pendapat para ulama dan studi literature yang mendalam. Hasil penelitian menunjukkan bahwa konsep moderasi dalam al-Qur'an tidak hanya terbatas pada aspek ibadah ritual, tetapi juga merentang ke dalam bidang akhlak, sosial, dan politik. Al-Qur'an menekankan pentingnya sikap tengah-tengah, menghindari ekstremisme, dan mengembangkan keadilan serta kebijaksanaan dalam berbagai unsur kehidupan manusia. Penelitian ini memberikan kontribusi pada pemahaman lebih luas terkait nilai dan prinsip moderasi dalam Agama Islam, sejalan dengan perspektif al-Qur'an. Implikasi temuan penelitian ini diharapkan dapat menjadi dasar bagi pengembangan pemikiran dan implementasi moderasi dalam konteks kehidupan sehari-hari, yang sejalan dengan ajaran Al-Qur'an. Kata kunci: Al-Qur’an, Tafsir, Moderasi Beragama